Influence of Religiosity, Income and Access to Information Media on Community Interest in Cash Waqaf in Magelang City - Mujahid Quraisy; Rina Istiqomawati; Emma Widianti (PT FORMOSA CENDEKIA GLOBAL, 2024)
The city of Magelang with a majority Muslim population with a population of 109,373 Muslims out of a total population of 128,020 people. The economic activity that is most widely carried out in Magelang City is large trading businesses, which can open up quite potential opportunities in collecting cash waqf funds. This research aims to determine whether religiosity, income and access to information media influence the interest in giving cash waqf to the people of Magelang City. The research method used is quantitative research. The data analysis technique uses using the F and t tests in conjunction with multivariate linear regression analysis and dummy variables. Using the Purposive Sampling approach, 150 respondents were given questionnaires to complete in order to collect data. The study's findings suggest that interest in providing cash waqf is not significantly impacted by the income variable in part. As indicated by the sig value equal to 0.00 < 0.05 for the religiosity variable and the sig value equal to 0.00 < 0.05 for the information media access variable, interest in providing financial waqf is partially significant in relation to these variables. The variables of religiosity, income, and access to information media simultaneously and strongly influence desire in contributing cash waqf, as indicated by the findings of the F test as shown by the significance level of 0.00 < 0.05